Composition compound of Cr-N coating deposited on an aluminum preliminary irradiated with nitrogen ions - Guglya, A.G.; Neklyudov, I.M.; Shkuropatenko, V.A.; Vanzha, A.F.; Virich, V.D. (Вопросы атомной науки и техники, 2005)
Ion-beam assisted technology was used for deposition of Cr-N coating on aluminum under simultaneous irradiation with 30 keV nitrogen ions at temperatures 200 and 300°C. Distribution of metal components in the coating and in the coating-substrate mixing zone was studied as regards process temperature and the degree of pretreatment of aluminum surface with nitrogen ions to doses of 1,7.10¹⁷ and 3,4.10¹⁷ ions/cm² . The results obtained with the use of secondary ion mass spectrometry prove that ion pretreatment of aluminum substrate causes drastic changes in distribution of metal components in the intermixing zone. As the dose of preirradiation of the substrate increases, we observe intermixing of Al with Cr. Besides, we have recorded an expanded peak of AlCr precipitation in the intermixing zone. The chromium coating contains some admixtures of CrN and Cr₂N uniformly distributed in the depth, with their maximum near the mixing zone. Thus, the effect of penetration of those elements grows stronger with the increase of process temperature. A possible diffusion mechanism of metal and gaseous components into the coating is discussed.